Trust Restoration Strategy Analysis Customers, Negative E-Wom Mitigation, and Corporate Image Restoration in The Case of PT Pertamina (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The case involving PT Pertamina emphasizes the importance of building consumer trust and maintaining the company's image in the energy sector. The crisis that occurred can have a negative impact on the company's reputation, especially amidst the rapid spread of information through electronic word-of-mouth (e-WOM). This study aims to examine strategies that can be used by PT Pertamina to restore public trust, handle negative e-WOM, and restore the company's image. The approach used is qualitative-descriptive, with data collection through literature reviews and digital media analysis. The findings show that open and honest communication, rapid response to consumer complaints, and the use of technology in analyzing data are key elements in image recovery efforts. In addition, consumer involvement, implementation of Corporate Social Responsibility (CSR) programs, and improving service quality have also proven effective in strengthening customer loyalty. By implementing this strategy consistently, PT Pertamina has the opportunity to build a positive image and establish a more solid relationship with the community.